Determining Significant Predictors of Blood Iron Concentration and Status in Pregnant Filipino Women Using Linear Models (2019)
The decrease in blood iron levels during pregnancy is a concern that needs to be addressed, especially among Filipinos where anemia prevalence is relatively high. This study assessed maternal age, gestational age, height, body weight during pregnancy, daily consumption of iron supplements or multivitamins, gravidity, parity, and estimated monthly household income as potential predictors of levels of hemoglobin (Hb), hematocrit (Hct), serum ferritin (SF), serum iron (SI), total iron binding capacity (TIBC), unsaturated iron binding capacity (UIBC), and transferrin saturation (TSAT) among 109 pregnant women residing in Quezon, Palawan using simple linear regression (SLR). Significant predictors were then incorporated into full models using multiple linear regression (MLR) following the hierarchical method. Results show that gestational age significantly contributed to predicting levels of blood iron (p < 0.05). Gestational age was negatively associated with Hb, Hct, SF, log10 SF, log10 SI, and TSAT but positively associated with TIBC and UIBC. Gestational age accounted for variations ranging from as low as 4% in log10 SI up to 35% in UIBC. Additionally, weight was positively associated with Hb (p = 0.016) and Hct (p = 0.027), parity was negatively associated with log10 SF (p = 0.031), and daily consumption of iron or multivitamin supplements was negatively associated with TIBC (p < 0.001) and UIBC (p < 0.001). These identified predictors can be used in the clinical settings to target high-risk women for treatment or intervention.